Moving beyond the risk paradigm: Using the Good Lives Model with offenders in denial of sexual offending. (April 2018) - Dealey, Jill
Denial of sexual offending is complex, and can hinder the development of a positive working relationship between an offender and the probation officer managing their case; it can also impact on the offender's wider life experience as they are stranded between their past offending and creating a new offence-free life. The theory of the Good Lives Model can be used as a tool to reduce both the tensions in this professional relationship and enable the offender to move forward, both in addressing their behaviour and establishing a non-offending life.